The Effectiveness of the General Procurement Plan Information System (SIRUP) Implementation within the Public Procurement Cycle at the Bawaslu Surabaya - Ardilla Novianti; Sri Trisnaningsih (International Journal of Economics, Management and Accounting, 2026)
This study aims to analyze the effectiveness of the General Procurement Plan Information System (SIRUP) in supporting procurement planning and transparency at Bawaslu Surabaya during the non-election period. Employing a qualitative descriptive approach, data were collected through interviews, observations, documentation, and literature review involving key informants from the procurement management unit. The findings reveal that SIRUP has enhanced administrative order, facilitated procurement monitoring, and improved public access to procurement information, thereby strengthening transparency and accountability. Nevertheless, several challenges remain, including limited human resources, frequent budget revisions requiring data updates, and technical system issues. The study concludes that strengthening operator capacity and improving digital infrastructure are essential to optimize SIRUP implementation and sustain good governance within election oversight institutions.